Characterization of hollow glass sphere reinforced epoxy composites: Dynamical mechanical analysis and morphology - Altan, Mihrigul; Kahraman, Yusuf; Gumus, Beril (CARL HANSER VERLAG, 2017)
Hollow glass spheres (HGS) have many application areas in the field of composite production due to their lightweight property together with having a sufficient strength. This study has the focus on adding the HGS to epoxy resin in different concentrations. The surface of the glass spheres were modified with silane prior to resin casting. The material characterization of the HGS filled epoxies was based on the silane presence and the HGS addition. Dynamic mechanical analysis was applied to observe the mechanical properties depending on the temperature of the composites. Morphological investigations were made to determine the interfacial adhesion between epoxy and the HGS. As a result of these, it was obtained that the HGS addition enhanced the stiffness of the material without a sharp reduction in the ductility. Silane was observed to be successful in improving the storage modulus below the glass transition temperature (Tg). However, the reduction in Tg was observed in high amount of modified HGS loading due to their interfering effect on the crosslink system of the epoxy.
Keywords: Hollow glass sphere; epoxy resin; silane; morphology; dynamic mechanical analysis; SYNTACTIC FOAMS; BEHAVIOR; FRACTURE; FEATURES; Materials Science